2012
DOI: 10.5551/jat.11601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PPIs and an H2 blocker on the Antiplatelet Function of Clopidogrel in Japanese Patients under Dual Antiplatelet Therapy

Abstract: Aim: Dual antiplatelet therapy (DAPT) with aspirin and clopidogrel is essential after percutaneous coronary intervention (PCI).Clopidogrel is a prodrug and changed into active metabolite by cytochrome p450 enzymes (CYPs), especially CYP2C19. Proton pump inhibitors (PPIs) are used for the prevention of aspirin-induced gastrointestinal bleeding. PPIs are also metabolized by CYP2C19, although the degree of its contribution is dependent on the kind of PPI. Omeprazole, a PPI, has been reported to weaken the antipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
(29 reference statements)
1
18
0
1
Order By: Relevance
“…Accordingly, some studies showed that omeprazole attenuates the antiplatelet effect of clopidogrel [13][14][15] but others did not confirm these findings [19,20] . In contrast, esomeprazole, lansoprazole, pantoprazole and rabeprazole did not affect platelet function in patients treated with clopidogrel [13,15,[19][20][21][22] . However, it is unclear whether these ex vivo findings have clinical importance, i.e., if the co-administration of clopidogrel with omeprazole or other PPIs will result in reduced protection against cardiovascular events.…”
Section: Introductionmentioning
confidence: 74%
“…Accordingly, some studies showed that omeprazole attenuates the antiplatelet effect of clopidogrel [13][14][15] but others did not confirm these findings [19,20] . In contrast, esomeprazole, lansoprazole, pantoprazole and rabeprazole did not affect platelet function in patients treated with clopidogrel [13,15,[19][20][21][22] . However, it is unclear whether these ex vivo findings have clinical importance, i.e., if the co-administration of clopidogrel with omeprazole or other PPIs will result in reduced protection against cardiovascular events.…”
Section: Introductionmentioning
confidence: 74%
“…3 Theoretically, famotidine is not metabolized by CYP2C19, and our study also demonstrated that the addition of famotidine did not affect the antiplatelet effect of clopidogrel. 8 Therefore, these findings strongly suggest that omeprazole does not affect clopidogrel efficacy. The larger number of patients analyzed in this study (n=138) would support the reliability of their results more strongly than the 2 aforementioned studies.…”
Section: Editorial Ppi and Clopidogrelmentioning
confidence: 73%
“…My group also conducted a crossover study to analyze the effects of concomitant use of omeprazole or rabeprazole in 25 patients during DAPT, in which platelet reactivity was measured with the VerifyNow system. 8 We reported that patients taking omeprazole exhibited slightly higher platelet reactivity than those taking rabeprazole, and that the reactivity under rabeprazole intake was similar to that detected in control patients not taking PPI. 8 Thus, these studies suggest that omeprazole might significantly, although slightly, decreased the antiplatelet function of clopidogrel in the Japanese population.…”
Section: Editorial Ppi and Clopidogrelmentioning
confidence: 87%
“…However, it is unknown whether H2RA treatment is effective for clopidogrel‐induced or dual antiplatelet drug‐induced gastric mucosal injury. In general, because most H2RAs, such as famotidine, ranitidine and nizatidine, are renally excreted and hepatic enzymes, such as CYP2C19, do not metabolize such H2RAs, no interactions with clopidogrel and H2RAs have been reported . Therefore, an H2RA may be an appropriate alternative for patients treated with clopidogrel to avoid drug–drug interaction.…”
Section: Discussionmentioning
confidence: 99%